Predicting the dispersal of SARS-CoV-2 RNA from the wastewater treatment plant to the coast. Issue 9 (September 2022) - Robins, Peter E.; Dickson, Neil; Kevill, Jessica L.; Malham, Shelagh K.; Singer, Andrew C.; Quilliam, Richard S.; Jones, Davey L.
Abstract: Viral pathogens including SARS-CoV-2 RNA have been detected in wastewater treatment effluent, and untreated sewage overflows, that pose an exposure hazard to humans. We assessed whether SARS-CoV-2 RNA was likely to have been present in detectable quantities in UK rivers and estuaries during the first wave of the Covid-19 pandemic. We simulated realistic viral concentrations parameterised on the Camel and Conwy catchments (UK) and their populations, showing detectable SARS-CoV-2 RNA concentrations for untreated but not for treated loading, but also being contingent on viral decay, hydrology, catchment type/shape, and location. Under mean or low river flow conditions, viral RNA concentrated within the estuaries allowing for viral build-up and caused a lag by up to several weeks between the peak in community infections and the viral peak in the environment. There was an increased hazard posed by SARS-CoV-2 RNA with a T 90 decay rate >24 h, as the estuarine build-up effect increased. High discharge events transported the viral RNA downstream and offshore, increasing the exposure risk to coastal bathing waters and shellfisheries – although dilution in this case reduced viral concentrations well below detectable levels. Our results highlight the sensitivity of exposure to viral pathogens downstream of wastewater treatment, across a range of viral loadings and catchment characteristics – with implications to environmental surveillance. Graphical abstract: Image 1 Highlights: SARS-CoV-2 RNA from treated sewage unlikely to be detectable in estuaries. SARS-CoV-2 RNA from untreated sewage can be detectable in estuaries. Peak RNA concentration in estuaries can be delayed from peak community infection. RNA concentration is sensitive to viral loading, decay, hydrology, and estuary shape. Abstract : Public health risk; Sewage discharge; Viral surveillance; Water pollution; Wastewater-based epidemiology.